DNA polymorphisms in chickpea accessions as revealed by PCR-based markers - Yadav, P; Koul, K K; Shrivastava, N; Mendaki, M J; Bhagyawant, S S (Cellular and Molecular Biology, 2015)
Chickpea is a food legume which is alleged to be a preferred source of protein next only to milk. Germplasm of cultivated chickpea available is deficient in desired genetic variation. Genetic manipulations therefore, necessitate the genetic exploitation of its related annual and wild species. 42 RAPD and 41 ISSR markers were employed to ascertain polymorphism across 20 genotypes which were collected from 10 different geographical areas of the world. RAPD marker detected 51% genetic polymorphisms while ISSR marker detected 54 %. With an average of 6.5 each RAPD primer amplified 5-8 bands. Similarly with an average of 7.9 each ISSR primer amplified 4-12 bands. The cluster dendrogram demonstrated a similarity coefficient range from 0.80 to 0.92 due to RAPD markers, whereas with ISSR primers the cluster dendrogram showed similarity coefficient of 0.60 to 1.00. Accessions from same geographical area seem to be genetically similar than those from geographically distant and isolated ones. When however compared, interestingly the ISSR dendrogram showed more correlation with pedigree data than the RAPD dendrogram. The variability index worked out in the present study ranges from 0.79 to 0.96. Since the ultimate reason for such studies is selection of diverse genetic accessions for their recommendation to breeding programmers, the accessions like ICC6263, ICC6306 and ICC17160 can be recommended as parents. Further breeding programmes can therefore be planned to procure additional variation complexes in chickpea genetic stocks.